A Review of Extensor Hallucis Longus Variants Featuring a Novel Extensor Primi Internodii Hallucis Muscle Merging With Extensor Hallucis Brevis - Zdilla, Matthew J. (J Foot Ankle Surg, 2018)
The extensor hallucis longus (EHL) muscle/tendon complex has been used in a variety of tendon transfer and tenodesis surgeries to correct iatrogenic hallux varus deformity, equinovarus foot deformity, clawed hallux associated with a cavus foot, and dynamic hyperextension of the hallux and, even, to prevent pedal imbalance after transmetatarsal amputation. Although it is usually considered a unipennate muscle inserting into the dorsum of the base of the distal phalanx of the hallux, a vast majority of EHL muscles possess ≥1 accessory tendinous slips that insert into other neighboring bones, muscles, or tendons, which can complicate these surgeries. The present report reviewed the reported data on EHL variants and describe a new variant, in which the tendons of the extensor primi internodii hallucis muscle of Wood and extensor hallucis brevis muscle merged together proximal to the tarsometatarsal (Lisfranc) joint, a site of rupture for extensor tendons of the foot. The reported variant might have contributed to the development of the clawed hallux seen in our patient and could complicate its operative management by mimicking the normal extensor digitorum longus tendon. Knowledge of the EHL variants and the particular muscular pattern described in the present review could improve the diagnosis and tendon transfer and tenodesis operative planning and outcomes.